Structural and dynamics studies of the TetR family protein, CprB from Streptomyces coelicolor in complex with its biological operator sequence - Bhukya, Hussain; Jana, Asis K.; Sengupta, Neelanjana; Anand, Ruchi (Journal of Structural Biology, 2017)
In Streptomycetes, tetracycline repressor family of transcription regulators (TetR-FTRs) controls various biological processes including antibiotic biosynthesis, cellular morphology and innate resistance. Here, we focus on understanding the structural basis of transcription regulation by CprB, a member of TetR-FTRs from S. coelicolor. CprB is implicated as a receptor of gamma-butyrolactones, a class of quorum sensing molecules, responsible for initiating secondary metabolic pathways. In order to understand the molecular mechanism of DNA recognition, the X-ray structure of CprB in complex with its biological relevant operator sequence was solved to a resolution of 3.95 angstrom. Furthermore, to refine and compliment the results, atomistic molecular dynamics simulations were carried out using the X-ray structure as the template. The studies reveal that CprB binds to DNA as dimer of dimers with this mode of interaction results in minimal distortion in the DNA, enabling these proteins to recognize multiple sequences with varying affinity. Another crucial finding from our simulation results was that the positively charged N-terminal arm of CprB brings extra stability to the protein-DNA complex by interacting with the minor-groove of the DNA and anchoring itself to the phosphate backbone. Corroborating electrophoretic mobility shift assay and fluorescence anisotropy experiments showed that the mutant AN6-CprB exhibited about 7-8 fold reduced DNA binding. Comparison with other TetR-FTRs reveals that this strategy is also employed by over 25% of TetR-FTRs, where N-terminal anchoring mechanism is used to enhance selectivity for a particular DNA sequence. (C) 2017 Elsevier Inc. All rights reserved.

β-catenin-driven innate and metabolic reprograming in macrophages fuel T-cell-dependent inflammation in Toxoplasma gondii infection: implications for therapeutic intervention - Kumari, Geetika; Kumar, Amit; Muduli, Rasmiranjan; Das, Mayami; Bhowmik, Prithwik; Singha, Biplab; Namdeo, Ankita; Dcosta, Criss; Wadhwa, Neerja; Maras, Jaswinder Singh; Kundu, Rakesh; Gupta, Nishith; et al. (Cell Death & Disease, 2026)
Toxoplasma gondii activates innate immunity via TLR11/12 in mice, but the lack of functional human counterparts leaves a gap in understanding parasite sensing in humans. Here, we bridge this gap by uncovering a host-intrinsic sensing mechanism, wherein beta-catenin signaling mediates immune recognition of T. gondii. Notably, this parasite hijacks the PI3K-AKT-beta-catenin pathway in macrophages to promote its replication. While beta-catenin ablation, either genetically or pharmacologically (XAV939), disavows this process, thereby inhibiting replication. Phospho-beta-catenin-TCF4 drives IRF4 transcription, followed by phosphorylation of IRF4, which regulates CYBB transcription. Augmented CYBB enhances mitochondrial-ROS and triggers mitophagy via PINK1/PARKIN, whereas ablation of beta-catenin preserves mitochondrial fitness, thereby impeding parasite growth. Enhanced ROS can oxidize host mitochondrial DNA, which then functions as a host-associated molecular pattern (HAMP). This activates the cytosolic pathogen recognition receptor (PRR) AIM2, triggering the AIM2-NLRP3-ASC-caspase-1-IL-1 beta inflammasome cascade. This cascade leads to gasdermin-D-mediated pyroptosis, a process that critically depends on the phosphorylation of beta-catenin. T. gondii's ASP5 protease plays an essential role in the phosphorylation of beta-catenin-mediated inflammasome activation. Metabolically, beta-catenin-dependent enhanced ROS stabilized HIF-1 alpha, which stimulates the HKII-LDH-A axis, promoting the Warburg effect, histone acetylation and pro-inflammatory M1-macrophage polarization (IL-12/IL-6/IL-23/TNF-alpha). beta-catenin ablation shifts metabolism to oxidative-phosphorylation, fostering M2-phenotype (IL-2/IL-10/TGF-beta) that abrogates parasites survival. beta-catenin also strengthens MHC-TCR avidity, driving Th1/Tc1, Th9/Tc9, and Th17/Tc17 paradigm, whereas beta-catenin inhibition promotes anti-inflammatory Th2/Tc2/Threg/Tcreg differentiation. Additionally, macrophage intrinsic beta-catenin dictates metabolic divergence in both CD4(+) and CD8(+)T-cells. Notably, beta-catenin-deletion in macrophages protects mice (beta-cat Delta M Phi) against infection, highlighting that XAV939 has therapeutic potential against toxoplasmosis.